The Effects of Melatonin Supplementation on Glycemic Control: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Doosti-Irani, Amin; Ostadmohammadi, Vahidreza; Mirhosseini, Naghmeh; Mansournia, Mohammad Ali; Reiter, Russel J.; Kashanian, Maryam; Rahimi, Maryam; Razavi, Maryamalsadat; Asemi, Zatollah (Hormone and Metabolic Research, 2018)
This systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted to clarify the effect of melatonin supplementation on glycemic control. Databases including PubMed, MEDLINE, EMBASE, Web of Science, and Cochrane Central Register of Controlled Trials were searched until July 30th, 2018. Two reviewers independently assessed study eligibility, extracted data, and evaluated the risk of bias for included trials. Heterogeneity among included studies was assessed using Cochran’s Q test and I-square (I2) statistic. Data were pooled using random-effect models and mean difference (MD) was considered as the overall effect size. Twelve trials out of 292 selected reports were identified eligible to be included in current meta-analysis. The pooled findings indicated that melatonin supplementation significantly reduced fasting glucose (MD=–6.34; 95% CI, –12.28, –0.40; p=0.04; I2: 65.0) and increased the quantitative insulin sensitivity check index (QUICKI) (MD=0.01; 95% CI, 0.00, 0.02; p=0.01; I2: 0.0). However, melatonin administration did not significantly influence insulin levels (MD=–1.03; 95% CI, –3.82, 1.77; p=0.47; I2: 0.53), homeostasis model assessment of insulin resistance (HOMA-IR) (MD=–0.34; 95% CI, –1.25, 0.58; p=0.37; I2: 0.37) or HbA1c levels (MD=–0.22; 95% CI, –0.47, 0.03; p=0.08; I2: 0.0). In summary, the current meta-analysis showed a promising effect of melatonin supplementation on glycemic control through reducing fasting glucose and increasing QUICKI, yet additional prospective studies are recommended, using higher supplementation doses and longer intervention period, to confirm the impact of melatonin on insulin levels, HOMA-IR and HbA1c.
Keywords: melatonin; glycemic control; insulin resistance; meta-analysis